Sweet Potato Production and the Impact of Information and Communication Technology (Ict) on Selected Chiefdoms in Moyamba District of Southern Sierra Leone - Ngegba, Mohamed Paul; Koroma, Muctar F.; Kamara, James (European Journal of Applied Sciences, 2022)
This study examined the impact of Information Communication Technology (ICT) devices on sweet potato yield in the Moyamba District of Southern Sierra Leone. The study's sample size was two hundred fifty (250) sweet potato farmers. The researchers adopted a multistage, purposive, and systematic sampling approach to select the sample size. Most sweet potato farmers frequently use radio, cell phones, televisions, videos, and WhatsApp devices for precious potato productivity. The involvement of women in sweet potato farming exceeds that of the men. in the study area. In conclusion, ICT technologies have increased sweet potato productivity per acre and improved and transformed sweet potato growers' livelihoods. The government and network providers should expand network coverages for radios, cell phones, television, and videos on sweet potato productivity. Moreover, the service agents should provide training and workshops to dear potato producers using ICT tools. Moreover, improve their operational methods and ensure network services are always available.